Lesões orais em crianças e adolescentes atendidos em Centros de Referência de Universidades Públicas Baianas - Pessôa, Camila Porto (2011)
This study aimed to identify oral lesions most frequently in children and adolescents in Reference Units of Oral Lesions of Public Universities of Bahia in the period 1996 to 2010, and estimate the association between socio-demographic factors and type of oral lesions. It is a cross-sectional study using data obtained from medical records, records of requests and reports of biopsies from patients seen at the Universidade Estadual de Feira de Santana and Universidade Federal da Bahia. Two papers were prepared, which varied in relation to the population studied and the type of data analysis used. The first article presents the thesis itself, including two data centers of research and analysis of potential effect modifiers and confounding through logistic regression modeling. The second article was written with the intention to present only the results at the Universidade Estadual de Feira de Santana, using bivariate analysis. The results showed that there is great variability of oral lesions that can affect children and adolescents. Sociodemographic profile of the patients studied varied with the type of lesion found. Using the analysis of confounding proved necessary. It could be concluded before the injuries found that the subject is poorly researched and relevant in the age group 0 to 19 years, requiring a greater number of publications in this regard.